If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + 3b + 2a = p Reorder the terms: 2a + 3b + c = p Solving 2a + 3b + c = p Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. 2a + 3b + -3b + c = -3b + p Combine like terms: 3b + -3b = 0 2a + 0 + c = -3b + p 2a + c = -3b + p Add '-1c' to each side of the equation. 2a + c + -1c = -3b + -1c + p Combine like terms: c + -1c = 0 2a + 0 = -3b + -1c + p 2a = -3b + -1c + p Divide each side by '2'. a = -1.5b + -0.5c + 0.5p Simplifying a = -1.5b + -0.5c + 0.5p
| X*2+3=7 | | -150=-2(-6n+7)+5 | | x^2-2x-8=16 | | 3(n)=200 | | 32q*q=72 | | 10(s-5)=-125 | | -2(-6+7)+5n=-150 | | x^2-76x-80=0 | | (200-2y)-y=50 | | x^2-76x-8-80=0 | | 2x-1=Q | | 2(x+5)=8x-5 | | 7x+6+3x-4= | | -13x-11/23 | | s=1/12(300) | | -5*-4=-29 | | 300=f/1.01 | | Y=4x^2+28x-32 | | 0.4(2x+1)=3[0.2x+(-2)]-4 | | 10x-3y=-0 | | 2(4s+6)=100 | | 300=12n | | 3(x-4)+2=3(x-1)-7 | | K^2-2k-89=-7 | | 2(45+6)=100 | | 8(2l+5)=168 | | 3x/9x^2 | | 10x+20=5x+10 | | 15x+21(x-4)=96 | | 4(a-9)=24 | | 2(5x-1)=12 | | 2(x+4)(x+4)=8 |